2018
DOI: 10.2478/ausp-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Parental Attitudes to Teacher Pronunciation in Very Early English

Abstract: Teaching English as a foreign language at an early (7–12) and even at a very early (under 7) age is becoming more and more popular and accessible, mainly due to the pressure from parents. Parents are essential stakeholders in the TEFL of these ages, and thus it is beneficial for the future of TEFL to do research into parental attitudes in order to be able to assure that expectations and outcomes meet. Our study examines parental attitudes towards the teacher and the ideal age to start learning a foreign langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the EFL context, the teacher quality has to get careful attention. Moreover, a study showed that EYL's parents suggest to emphasizing on native-like pronunciation from English teachers (Bozsó & Nagy, 2018). Through the previous studies of teachers' and students' pronunciation have indicated some factors which affect the pronunciation quality as so-called RP (received pronunciation) like institutional sociocultural context (Bozsó & Nagy, 2018), motivation ( Aratusa, 2019;Astina;Reid & Debnarova, 2020), error correction (Couper, 2019;Febrianto, 2021;A.…”
Section: Intelligibility Of English Vocabulary For Young Learners In ...mentioning
confidence: 99%
“…In the EFL context, the teacher quality has to get careful attention. Moreover, a study showed that EYL's parents suggest to emphasizing on native-like pronunciation from English teachers (Bozsó & Nagy, 2018). Through the previous studies of teachers' and students' pronunciation have indicated some factors which affect the pronunciation quality as so-called RP (received pronunciation) like institutional sociocultural context (Bozsó & Nagy, 2018), motivation ( Aratusa, 2019;Astina;Reid & Debnarova, 2020), error correction (Couper, 2019;Febrianto, 2021;A.…”
Section: Intelligibility Of English Vocabulary For Young Learners In ...mentioning
confidence: 99%
“…Within the EFL setting, the instructor quality needs to be cautious consideration. Additionally, a consideration appeared that EYL's guardians recommend emphasizing native-like articulation from English instructors (Bozsó & Nagy, 2018). Past studies on teachers' and students' articulation have identified several factors that influence the quality of pronunciation, such as the adherence to Received Pronunciation (RP) and the sociocultural context of the educational environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the sociocultural setting plays a crucial role in shaping articulation, as it encompasses diverse linguistic influences and social norms that impact language use within educational settings. Understanding these factors is essential for educators to navigate the complexities of language instruction and promote effective communication skills among students (Bozsó & Nagy, 2018), inspiration (Aratusa, 2019;Astina, 2020;Reid & Debnarova, 2020), blunder rectification (Couper, 2019;Febrianto, 2021;A. P. Gilakjani et al, 2019;P.…”
Section: Introductionmentioning
confidence: 99%